Distribution of USDA SAFE CRP Farms in Relation to Historically Documented Populations of the Federally Endangered Karner Blue Butterfly in Eau Claire County, WI - Henden, Jacob (My University, 2015)
We wanted to analyze the spatial relationship between private land enrolled in the USDA State Acres for Wildlife Enhancement (SAFE) Conservation Reserve Program and historically documented Karner Blue butterfly (Lycaeidesmelissasamuelis) populations in Eau Claire County. This analysis was done using ArcMap 10.2. Results will be provided to the USDA.
Color poster with text, maps, photographs, and images.
Keywords: Wildlife conservation; Wild lupine; Lycaeides melissa samuelis; Karner Blue butterfly; Posters